ASSESSING COMPLIANCE TO COVID-19 PROTOCOLS AMONG LICENSED HOSPITALITY PROVIDERS IN THE HO MUNICIPALITY OF THE VOLTA REGION OF GHANA - Dabi, Michael; Ankrah, Eric Tackie Tawiah (Technium BioChemMed, 2021)
The present study assessed compliance with COVID-19 prevention protocols in the hospitality industry in the Ho Municipality of the Volta Region of Ghana. The study employed secondary data gathered in February 2021 from a 3-day field exercise undertaken by the Ghana Tourism Authority on the compliance of the Safety Protocols on the COVID-19 pandemic by operators in the hospitality industry. A total of sixty units (20 hotels, 20 local restaurants, and 20 Drinking Bars) were selected using a mixture of probability and non-probability sampling techniques such as stratified, purposive, and simple random sampling. The resulting data gathered using structured questionnaire and observations were coded and entered into SPSS for analysis. Results showed that all sectors and units were adhering to the proposed safety protocols to an appreciable extent. The study made recommendations in line with WHO standard protocols for preventing the spread of the virus and regular monitoring of hospitality facilities in the municipality and beyond to ensure compliance.